The role of souvenirs in enhancing local cultural sustainability: a systematic literature review - Qiu, Liping; Abdul Rahman, Ahmad Rizal; Dolah, Mohd Shahrizal (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Souvenirs can facilitate the dissemination and promotion of culture, and culture gives souvenirs unique characteristics and cultural connotations. With the increasingly competitive academic environment, an in-depth understanding of the relationship between souvenirs and local culture is crucial to the theory and practice of souvenir and local culture-development research. The main purpose of this study is to review the previous literature that articulates the dynamic relationship of interdependence and development between souvenirs and local culture. Based on a systematic literature review, the data for this study came from a review of 35 documents between 2019 and 2024. The documents were then analysed individually using the ATLAS.ti 24 program. The analysis revealed five central themes: (1) sustainability and innovation; (2) authenticity and experience; (3) economic and community impact; (4) cultural identity expression; and (5) consumer behaviour and technology. These themes illuminate that souvenirs are not only cultural ambassadors, but also play a critical role in economic development, cultural preservation, and consumer engagement. The findings provide new directions for future research and actionable insights for practitioners, researchers, and designers who enhance the sustainability of local culture through souvenirs. This review contributes to a deeper understanding of the dynamic interactions between souvenirs and local cultures and proposes a framework for the sustainable development of souvenirs.